Does it matter how people speak? - Alberto Chong (Inter-American Development Bank, Research Department, 2006)
Language serves two key functions. It enables communication between agents, which allows for the establishment and operation of formal and informal institutions. It also serves a less obvious function, a reassuring quality more closely related to issues linked with trust, social capital, and cultural identification. While research on the role of language as a learning process is widespread, there is no evidence on the role of language as a signal of cultural affinity. I pursue this latter avenue of research and show that subtle language affinity is positively linked with change in earnings when using English-speaking data for cities in the Golden Horseshoe area in Southern Ontario during the period 1991 to 2001. The results are robust to changes in specification, a broad number of empirical tests, and a diverse set of outcome variables.
Keywords: O40; Z13; O51; 330; Linguistics; Culture; English; Trust; Governance; Institutions; Canada; Sprache; Kommunikation; Kulturpsychologie; Vertrauen; Englisch (Sprache); Kanada; Schätzung; Ontario (Provinz)